On a random lead time and threshold shock model using phase‐type geometric processes. (8th February 2018) - Sarada, Y.; Shenbagam, R.
Abstract : This study investigates two random threshold shock models for a repairable deteriorating system with nonnegligible maintenance times, with and without a spare via a phase‐type geometric process. The system fails whenever the intershock arrival time is less than a random threshold. The provision of stochastic lead time is incorporated in Model II so that an ordering policy N −1 and a replacement policy N based on the number of failures of the system are also considered. An explicit expression of the average cost rate is derived for both models and the optimal replacement policy N * is obtained by minimizing the long‐run average cost rate analytically. The numerical illustrations and sensitivity analysis provided therein conform to the observations made in the study.